2013
DOI: 10.1371/journal.pone.0067152
|View full text |Cite
|
Sign up to set email alerts
|

Serum Uric Acid and Non-Alcoholic Fatty Liver Disease in Non-Diabetic Chinese Men

Abstract: Increased serum uric acid (SUA) levels may be involved in the development of non-alcoholic fatty liver disease (NAFLD) in men presenting with metabolic syndrome (MetS) and/or insulin resistance. We aimed to determine the independent relationship between SUA and NAFLD in non-diabetic Chinese male population, and to explore the determinants of SUA levels among indexes of adiposity, lipid, and genotypes pertaining to triglycerides metabolism, inflammation, oxidative stress, and SUA concentrations. A total of 1440… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
36
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 41 publications
7
36
0
2
Order By: Relevance
“…There is a graded, positive association between SUA levels and NAFLD severity and elevated SUA levels predict NAFLD risk independently of coexisting MetS features in different ethnicities. [99][100][101][102][103][104][105][106][107][108] Accordingly, a large study found that increased SUA levels were associated with cirrhosis and elevated serum liver enzymes, independent of potential confounders, in 5,518 participants during a mean follow-up of 12.9 years. 96 Further studies are needed to ascertain whether reducing SUA levels would prevent NAFLD/NASH development and progression.…”
Section: Metabolic Syndromementioning
confidence: 99%
“…There is a graded, positive association between SUA levels and NAFLD severity and elevated SUA levels predict NAFLD risk independently of coexisting MetS features in different ethnicities. [99][100][101][102][103][104][105][106][107][108] Accordingly, a large study found that increased SUA levels were associated with cirrhosis and elevated serum liver enzymes, independent of potential confounders, in 5,518 participants during a mean follow-up of 12.9 years. 96 Further studies are needed to ascertain whether reducing SUA levels would prevent NAFLD/NASH development and progression.…”
Section: Metabolic Syndromementioning
confidence: 99%
“…In Indian population, Paul et al, in their study found that hyperuricemia reflects oxidative stress and is associated with disease progression which can serve as surrogate marker for CLD with varied etiology [5]. Xie et al, documented crucial role of hyperuricemia is an important independent risk factor for NAFLD in Chinese population [4]. Shih et al, observed significant association between serum uric acid levels and NAFLD among US population; independent of multiple metabolic risk factors [15].…”
Section: Discussionmentioning
confidence: 99%
“…In cirrhotic liver, the Extra Cellular Matrix (ECM) produced by myofibroblasts which are trans-differentiated from activated Hepatic Stellate Cells (HSCs) differs qualitatively and quantitatively compared to normal liver. An increase in fibril and non fibril forming collagens along with glycoproteins, proteoglycans and glycosaminoglycans reflects ECM turnover and serve as direct biomarkers for severity of cirrhosis [3].Inflammatory factors [Tumor Necrosis Factor α (TNF-α) and interleukins] induced oxidative and apoptotic stress are important features for liver fibrosis/cirrhosis progression which results in uric acid production, an end product of purine metabolism [4]. Hyperuricemia, increased degradation of nuclear material cause endothelial dysfunction, insulin resistance, oxidative stress and systemic inflammation (metabolic syndrome) which are risk factors for hepatic damage [5].…”
mentioning
confidence: 99%
“…Convencionalmente se ha asociado la hiperuricemia con el desarrollo de gota, tofos y nefrolitiasis. Sin embargo, existe evidencia emergente que la asocia con el desarrollo de obesidad, diabetes mellitus tipo 2 (DM2), síndrome metabólico (SMet), enfermedad cardiovascular [3][4][5][6][7][8] y, aunque aún controversial, con la generación de enfermedad del hígado graso no alcohólica (EHGNA) 9,10 . Por esta razón, diversos grupos de investigación han postulado que los valores elevados de AU pueden contribuir directamente con la activación de la inflamación sistémica como trastorno desencadenador de enfermedades cardiovasculares y metabólicas [11][12][13][14] .…”
Section: Introductionunclassified